2018
DOI: 10.1016/j.biortech.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Economic assessment of biodiesel production from wastewater sludge

Abstract: Currently, there are mainly two pathways of the biodiesel production from wastewater sludge including 1) directly extracting the lipid in sludge and then converting the lipid to biodiesel through trans-esterification, and 2) employing sludge as medium to cultivate oleaginous microorganism to accumulate lipid and then transferring the lipid to biodiesel. So far, the study was still in research stage and its cost feasibility was not yet investigated. In this study, biodiesel production from wastewater sludge was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In this process plant, typical scheme of calculations was used, which often are used as rule of thumb for such bioprocesses. The scheme of calculation of plant direct cost was taken from Chen et al (2018).…”
Section: Equipment Purchase Costmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process plant, typical scheme of calculations was used, which often are used as rule of thumb for such bioprocesses. The scheme of calculation of plant direct cost was taken from Chen et al (2018).…”
Section: Equipment Purchase Costmentioning
confidence: 99%
“…(6). and n are cost of reference equipment, scale information about reference equipment and size exponent factor respectively, available in the literature (Chen et al, 2018;Ram et al, 2018;Sweeting, 1997). Plant capacity affects the unit cost of production (Table 6).…”
Section: Plant Capacitymentioning
confidence: 99%
“…The current work has employed the unit production cost metric as the preferred economic assessment tool, which is defined as the total annualised cost per unit mass of the specified product. This is because this economic assessment approach is widely utilised in the economic assessment of engineering systems more so as it enables an easy comparison of different production processes [22,45,46]. The unit cost of production, C, in US$/kg-biodiesel was determined, as follows [22],…”
Section: Capital Cost Componentsmentioning
confidence: 99%
“…Refermentation of sludge is a promising way to increase lipid content and enhance sludge reduction [ 40 ]. Additionally, it was found that biodiesel production from lipid accumulated by sludge fermentation had economic and energetic feasibility, and it was principally depending on the amount of sludge reduction and lipid accumulation [ 6 , 60 ].…”
Section: Introductionmentioning
confidence: 99%